THE EFFECT OF WORK ENVIRONMENT AND WORKLOAD ON THE PERFORMANCE OF ADMINISTRATIVE EMPLOYEES PT. SAMINDO UTAMA KALTIM - Misrika Sepliani Putri; Askiah Askiah; Joko Widiarto; Joko Sabtohadi (LPSDI Bina Patria, 2022)
The purpose of this study was to determine the effect of the work environment and workload on the performance of administrative employees of PT. Samindo Utama East Kalimantan. The research was conducted on 35 employees as respondents. The data analysis method used in this research is questionnaire testing conducted by testing the validity and reliability, and hypothesis testing is done using a multiple linear regression test, T-test, F test, and coefficient of determination. Based on the results of data analysis with the help of the SPSS program. The results of the t-test indicate that the work environment variable (X1) has a positive but not significant effect on the performance of the administrative employees of PT. Samindo Utama Kaltim and the workload variable (X2) have a positive and significant effect on the performance of the administrative employees of PT. Samindo Utama East Kalimantan. The results of the F test are known from the significance value for the effect of X1 and X2 simultaneously on Y, which is 18%, while other factors influence 82%.